DEFENSA DEL RECURSO ALIMENTICIO POR ASTYLUS RUBRICOSTATUS GERMAR, 1824 (INSECTA: COLEOPTERA: MELYRIDAE) - Sosa, Claudio Alejandro; Manfrini de Brewer, Mireya (Acta Entomológica Chilena, 2022)
Adults of Astylus rubricostatus deferid inflorescences of the herb Gaillardia megapotamica var radiata (Griseb) Baker against intrusión by conspecific individuáis. It is probable that the behaviour is a result from competition among individuáis of both sexes for the amount of polen contained by flowers of G. megapotamica, which seems to be the limiting resource.